Cosmic-Ray Flux Correlation between MCMU and JBGO Neutron Monitors - A. Kittiya; W. Nuntiyakul; A. Seripienlert; S. Madlee; W. Sonsrettee; P. Evenson; D. Ruffolo; A. Sáiz; S. Oh; J. Jung; Q. Q. Shi; S. Wang; et al. (The Astrophysical Journal, 2024)
Neutron monitors (NMs) are large ground-based detectors of atmospheric secondary particles, mostly neutrons, from primary cosmic rays. Their sky direction and rigidity imply a well-defined incoming (asymptotic) direction in space. From 2015 December 16 to 2017 January 8, 6 of the 18 NM counters had been transferred from McMurdo to Jang Bogo, both in Antarctica, so data from similar detectors were recorded simultaneously at these two nearby NM stations. Autocorrelations of these NM count rates are well fit as the sum of three components: an exponential function and a cosine with a period of 1 day, both centered at zero lag, plus a constant. Fitting the cross correlation of the two count rates, the functions are no longer centered at zero lag. The best-fit cosine phase is at time lag −160.22 ± 0.12 minutes. Calculating cosmic-ray trajectories in Earth's magnetic field throughout the time interval, the mean difference in response-weighted asymptotic longitudes corresponds to time lag −169.41 ± 0.31 minutes, in close agreement with the observed lag. Thus, the cosine term is consistent with and provides a technique to cleanly measure the cosmic-ray anisotropy. In contrast, the peak term shows a time lag of –14.55 minutes, much closer to the –9.60 minutes lag in rotation due to the difference in geographic longitude. We find a similar behavior in the correlations between other pairs of stations. We propose that rapid fluctuations in the counting rate may be primarily due to cosmic-ray particles of very high energy.